Using ecological niche modelling to identify the high-quality ecological areas of Houttuynia cordata Thunb. based on secondary metabolites content - Zhang, Xiaoting; Zhou, Jingyi; Xu, Huizhong; Peng, Cheng; Meng, Fanyun (Frontiers in Plant Science, 2025)
IntroductionHouttuynia cordata Thunb. (H. cordata), as a key ingredient in Lianhua Qingwen capsules, plays a critical role in enhancing the antiviral and anti-inflammatory efficacy of the prescription due to its heat-clearing and detoxifying properties, and has contributed significantly to the prevention and control of the COVID-19 pandemic. However, the increasing demand for H. cordata - containing Chinese patent medicines and preparations has led to a continuous decline in its wild reserves, which are now insufficient to meet industrial production needs. Current research predominantly focuses on component identification, while the mechanisms underlying the effects of environmental factors on the accumulation of secondary metabolites (SMs) remain poorly understood.MethodsThis study innovatively integrates ecological suitability with a spatial quality assessment system. By employing the Biomod2 ensemble modeling platform to predict the habitat suitability of H. cordata and combining path analysis with Kriging interpolation to quantify causal relationships between environmental variables and SMs (including 2-undecanone, quercitrin, and quercetin), we delineated high-quality ecological zones to guide the site selection of artificial cultivation bases.ResultsKey findings include: (1) Ecological suitability zones for H. cordata are predominantly concentrated in regions south of the Yangtze River Basin and west of the Hengduan Mountains (e.g., Yunnan-Guizhou Plateau, Sichuan Basin), with annual precipitation (Bio12) and human activities (human footprint, population density) identified as primary drivers. (2) The spatial distribution of three SMs exhibited marked heterogeneity, with no overlapping regions simultaneously achieving high contents of all three metabolites.DiscussionThis spatial divergence underscores the necessity for differentiated cultivation planning based on the pharmacological requirements of target SMs to optimize medicinal value.